2007
DOI: 10.1021/ol701761t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Selenapenams, Selenacephems, and Selenazepines Using a 2-(Trimethylsilyl)ethyl Protection Approach

Abstract: Selenapenams, selenacephems, and selenazepines were synthesized using a 2-(trimethylsilyl)ethyl (TSE) protection approach in an extremely simple way. TSE protection for selenium is used for the first time in the synthesis of selenium-containing beta-lactam. Novel intramolecular cycloaddition reaction of selenium with alkynes and allenes is used in the present synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Our group has demonstrated the utility of the TSE protection approach for the synthesis of variety of selenium-containing bicyclic β-lactams. [4,9] Compound 6 ( Table 2) was therefore selected as an important starting material for the insertion of the propargylseleno moiety at the C(4) position in the azetidin-2-one system. Selective removal of the TSE group of 6 and subsequent in situ alkylation of the selenolate anion was attempted for the synthesis of the key intermediates 7 having propargylseleno moieties at their C(4) positions (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has demonstrated the utility of the TSE protection approach for the synthesis of variety of selenium-containing bicyclic β-lactams. [4,9] Compound 6 ( Table 2) was therefore selected as an important starting material for the insertion of the propargylseleno moiety at the C(4) position in the azetidin-2-one system. Selective removal of the TSE group of 6 and subsequent in situ alkylation of the selenolate anion was attempted for the synthesis of the key intermediates 7 having propargylseleno moieties at their C(4) positions (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there are only four reports on the preparation of seven-membered selenium-containing heterocycles (that is, 1,3-selenazepines), [4,9,11] whereas there is only one report for the synthesis of eight-membered selenium heterocycles such as 1,3-selenazocine, by our group. [8] This RCEYM approach allows the synthesis of previously inaccessible selenium-containing heterocycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the revolutionary and magical development reported by Schiesser et al [21,22] in incorporation of selenium in penam and cephalosporin nuclei provides some novel compounds of potential biological significance. Very recently, Koketsu et al [23,24] have reported 2-(trimethylsilyl)ethyl (TSE)-protection approach for the synthesis of bicyclic seleno-b-lactams, which further involves intramolecular cycloaddition reaction of selenium with alkynes and allenes. Thus, most recent trend in the b-lactam research has emerged, is the substitution of sulfur group with selenium and synthesis of this heterocycle with variety of substitutents at C-3, C-4 as well as N-1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the continuing interest in penam derivatives is shown by the elaboration of new methods for their preparation (e.g. [17]), the synthesis of analogs such as selenapenams [18], and the modifcation of known compounds, e.g., 6-aminopenicillic acid (6-APA) [19].…”
mentioning
confidence: 99%